2018
DOI: 10.1111/pce.13470
|View full text |Cite
|
Sign up to set email alerts
|

The light‐induced transcription factor FtMYB116 promotes accumulation of rutin in Fagopyrum tataricum

Abstract: Tartary buckwheat (Fagopyrum tataricum) not only provides a supplement to primary grain crops in China but also has high medicinal value, by virtue of its rich content of flavonoids possessing antioxidant, anti‐inflammatory, and anticancer properties. Light is an important environmental factor that can regulate the synthesis of plant secondary metabolites. In this study, we treated tartary buckwheat seedlings with different wavelengths of light and found that red and blue light could increase the content of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 54 publications
4
34
0
Order By: Relevance
“…The promoter sequences of those differentially expressed genes were obtained from Rice Genome Annotation Project (Kawahara et al, 2013). Promoter analysis of the G-box and PBE motif were performed as previously described (Zhang et al, 2019). GO enrichment was analyzed using agriGO as described by Du et al (2010).…”
Section: Generation Of Overexpression and Mutant Linesmentioning
confidence: 99%
“…The promoter sequences of those differentially expressed genes were obtained from Rice Genome Annotation Project (Kawahara et al, 2013). Promoter analysis of the G-box and PBE motif were performed as previously described (Zhang et al, 2019). GO enrichment was analyzed using agriGO as described by Du et al (2010).…”
Section: Generation Of Overexpression and Mutant Linesmentioning
confidence: 99%
“…It’s reported that BBX proteins play a vital role in plant growth and developmental processes, especially in seeding photomorphogenesis ( Gangappa & Botto, 2014 ). We investigated the transcript expression patterns at the different developmental tissues and under different treatments to study the biological roles of FtBBX genes in the Tartary buckwheat growth and development, based on the published Supplemental Data sets ( Zhang et al, 2019 ; Wu et al, 2017 ; Zhang et al, 2017a ; Li et al, 2019 ). The expression data of these FtBBX genes are presented in the form of a heat map that was constructed using HeatMap IIustructor program of TBtools software based on the Log2(FPKM) value of genes.…”
Section: Resultsmentioning
confidence: 99%
“…The transcript expression patterns ( Fig. 5A ) of 28 FtBBX genes were investigated under different light treatment for 48h including dark (D48), far-red light (FR48), blue light (B48), and red light (R48) using the published Supplemental Data sets ( Zhang et al, 2019 ). Except for FtBBX1 , FtBBX7 , FtBBX10 , and FtBBX21 , other genes were expressed in all samples, but the expression patterns of each gene were different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA-seq data for seedlings exposed to different wavelengths of light were obtained [61] ( Supplemental Table S1). As shown in Figure 5(B), the eight FtLOX genes were grouped into two clusters.…”
Section: Expression Patterns Of Ftlox Genes In Response To Lightmentioning
confidence: 99%